Head Stability and Head-Trunk Coordination in Horseback Riders: The Contribution of Visual Information According to Expertise - Olivier, Agnès; Faugloire, Elise; Lejeune, Laure; Biau, Sophie; Isableu, Brice (Frontiers in Human Neuroscience, 2017)
Maintaining equilibrium while riding a horse is a challenging task that involves complex sensorimotor processes. We evaluated the relative contribution of visual information (static or dynamic) to horseback riders’ postural stability (measured from the variability of segment position in space) and the coordination modes they adopted to regulate balance according to their level of expertise. Riders’ perceptual typologies and their possible relation to postural stability were also assessed. Our main assumption was that the contribution of visual information to postural control would be reduced among expert riders in favor of vestibular and somesthetic reliance. Twelve Professional riders and 13 Club riders rode an equestrian simulator at a gallop under four visual conditions: (1) with the projection of a simulated scene reproducing what a rider sees in the real context of a ride in an outdoor arena, (2) under stroboscopic illumination, preventing access to dynamic visual cues, (3) in normal lighting but without the projected scene (i.e., without the visual consequences of displacement) and (4) with no visual cues. The variability of the position of the head, upper trunk and lower trunk was measured along the anteroposterior (AP), mediolateral (ML) and vertical (V) axes. We computed discrete relative phase to assess the coordination between pairs of segments in the anteroposterior axis. Visual field dependence-independence was evaluated using the Rod and Frame Test (RFT). The results showed that the Professional riders exhibited greater overall postural stability than the Club riders, revealed mainly in the AP axis. In particular, head variability was lower in the Professional riders than in the Club riders in visually altered conditions, suggesting a greater ability to use vestibular and somesthetic information according to task constraints with expertise. In accordance with this result, RFT perceptual scores revealed that the Professional riders were less dependent on the visual field than were the Club riders. Finally, the Professional riders exhibited specific coordination modes that, unlike the Club riders, departed from pure in-phase and anti-phase patterns and depended on visual conditions. The present findings provide evidence of major differences in the sensorimotor processes contributing to postural control with expertise in horseback riding.